PELATIHAN SAFETY MANAGEMENT SYSTEM BAGI PEGAWAI UNIT PENYELENGGARA BANDAR UDARA - Mas, Ayu; Cahyono, Dwi; Amalia, Direstu (Universitas katolik Musi Charitas, 2020)
The Airport Management Unit (UPBU) as one of the flight service providers whose obliged tomake, implement, evaluate and improve continuously the Safety Management System (SMS). TheUPBU must be supported by competent personnel of SMS. In order to meet the needs of personnelin SMS, Palembang Aviation Polytechnic collaborates with the Secretariat General of AirTransportation, organized community service activities through SMS training which was heldonline. This activity is aimed at participants are able to explain the concepts of SMS and applythem in their respective work according to national and international standards. This activity wasattended by 19 UPBU employees from all regions of Indonesia and 1 person from the PalembangAviation Polytechnic. The results obtained indicate that training was run effectively from thequestionnaire evaluation of participants. There is an allocation of examination time and internetconnectivity need to be improved from this activity and internet connectivity is one of the importantfactors that support the smooth running of online learning activities.